2014
DOI: 10.5120/16957-7028
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of RoF PON System based on Orthogonal Frequency Division Multiplexing Technique

Abstract: The requirement of high bandwidth, high flexibility, high mobility and high data rate at lower cost can be met with a real convergence of radio over fiber (RoF) and orthogonal frequency division multiplexing (OFDM) techniques. This paper compares the results of OFDM as a modulation for radio over fiber in passive optical network (PON) for 288km single mode fiber with that of dispersion compensator fiber. The four optical network units (ONUs) are connected by using 1:4 ratio passive optical splitter. A laser so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Talli and Townsend [7] proposed Hybrid DWDM-TDM long-reach PON for next-generation optical access. Pehraj et al [8] have shown that the requirement of high bandwidth, high flexibility, high mobility and high data rate at lower cost can be met with a real convergence of radio over fiber (RoF) and orthogonal frequency division multiplexing (OFDM) techniques. To increase the bandwidth Alateeq et al [9] present a Design of Broadband RoF PON for the Last Mile, Zhang et al [10] proposed a novel architecture for nextgeneration passive optical network (PON) based on electrical code division multiplexing orthogonal frequency division multiplexing (ECDM-OFDM) access.…”
Section: Related Workmentioning
confidence: 99%
“…Talli and Townsend [7] proposed Hybrid DWDM-TDM long-reach PON for next-generation optical access. Pehraj et al [8] have shown that the requirement of high bandwidth, high flexibility, high mobility and high data rate at lower cost can be met with a real convergence of radio over fiber (RoF) and orthogonal frequency division multiplexing (OFDM) techniques. To increase the bandwidth Alateeq et al [9] present a Design of Broadband RoF PON for the Last Mile, Zhang et al [10] proposed a novel architecture for nextgeneration passive optical network (PON) based on electrical code division multiplexing orthogonal frequency division multiplexing (ECDM-OFDM) access.…”
Section: Related Workmentioning
confidence: 99%